BEATING BROKE BY GETTING OUT? EXAMINING THE RELATIONSHIP BETWEEN PERSONAL DEBT AND COMMUNITY-OUTMIGRATION - Gerhardt, Alyssa; Foster, Karen (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2021)
Scholarship on young people’s geographical mobilities tells us that young adults move away from their childhood communities for a complex mix of economic “push-pull” reasons, including relationships, aspirations, attachments to place, identity, and belonging. In this abundant research, particularly that which focuses on youth outmigration from rural and peripheral communities, there is surprisingly little attention paid to an issue that is top-of-mind for many young adults today: personal debt. In this paper, we draw insights from extant literature on youth mobilities to make the case for a greater examination of the role of personal debt in young people’s migration decisions. We hypothesize that youth and debt increase a person’s likelihood of moving away from peripheral regions. We test this hypothesis using data from a 2019 survey of Atlantic Canadians and find some support for it, and some interesting nuance, suggesting that there is good reason to examine debt’s role in youth mobilities in greater detail.